NOTIFIKASI PENGAMBILAN SAHAM OLEH KPPU DALAM UPAYA MENJALANKAN FUNGSI PENGAWASAN BERDASARKAN HUKUM PERSAINGAN USAHA - Ridha Hitalalla Hayuningtyas Soetomo; Nyulistiowati Suryanti; Sudaryat (Paulus Law Journal, 2023)
Based on Law Number 5 the Year 1999, KPPU has the function of supervising business competition in Indonesia. The supervision is carried out, among others, on the acquisition of shares through the notification system. The purpose of this study is to find out, determine, and formulate the practice of implementing the notification system in share takeovers (acquisitions) concerning KPPU's supervisory efforts in the context of preventing monopolistic practices and unfair business competition. This research uses descriptive-analytical specifications by examining a matter that has a relationship with the existing problems. The approach method used is juridical-normative which is a research approach that focuses on literature study. The results of this study concluded that the supervisory function by KPPU on the acquisition of shares is carried out using two systems, namely Pre-Notification and Post-Notification, so there is legal dualism.